ตัวแบบพัฒนาประสิทธิผลการปฏิบัติงาน ของเทศบาลตำบลกลุ่มพัฒนาจังหวัดร้อยแก่นสารสินธุ์ Model Development for Improving the Performance Efficiency of Sub-district Municipalities in the Roy-Kaen-Sarn-Sin Provincial Group - ผางจันทร์ดา, พุทธพงศ์; เคณาภูมิ, สัญญา (Chophayom Journal, 2018)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์ 1) เพื่อศึกษาระดับประสิทธิผลการปฏิบัติงานของเทศบาลตำบล 2) เพื่อศึกษาปัจจัยเชิงสาเหตุส่งผลต่อประสิทธิผลการปฏิบัติงานของเทศบาลตำบล 3) เพื่อสร้างตัวแบบพัฒนาประสิทธิผลการปฏิบัติงานของเทศบาลตำบล โดยทำการศึกษากลุ่มพัฒนาจังหวัดร้อยแก่นสารสินธุ์ การวิจัยระยะที่ 1 ศึกษาระดับประสิทธิผลการปฏิบัติงานและปัจจัยเชิงสาเหตุที่ส่งผลต่อประสิทธิผลการปฏิบัติงานของเทศบาลตำบล เป็นการวิจัยผสมผสานวิธีทั้งเชิงปริมาณและเชิงคุณภาพ กลุ่มตัวอย่าง ได้แก่ ตัวแทนผู้บริหาร ตัวแทนสมาชิกสภาเทศบาลตัวแทนปลัดเทศบาล ตัวแทนผู้อำนวยการกองคลัง ตัวแทนผู้อำนวยการกองช่าง และตัวแทนภาคประชาชน จำนวน 249 แห่ง วิเคราะห์ข้อมูลด้วยสถิติเชิงพรรณนา และการวิเคราะห์อิทธิพลเส้นทาง และการสัมภาษณ์เชิงลึกผู้ทรงคุณวุฒิ จำนวน 12 คน ใช้การวิเคราะห์เนื้อหา ระยะที่ 2 การสร้างตัวแบบเชิงยืนยันของปัจจัยที่ส่งผลต่อประสิทธิผล การปฏิบัติงานของเทศบาลตำบล และระยะที่ 3 การยืนยันตัวแบบเชิงยืนยันของปัจจัยที่ส่งผลต่อประสิทธิผลการปฏิบัติงานของเทศบาลตำบล โดยผู้มีความเชี่ยวชาญเฉพาะเรื่องตาม Expert Verified จำนวน 20 คน และวิเคราะห์ข้อมูลด้วยสถิติเชิงพรรณนา ผลการวจิ ัยพบวา่ 1) ระดบั ประสทิ ธผิ ลการปฏิบตั งิ านของเทศบาลตาํ บลกลมุ่ พฒั นาจงั หวัดรอ้ ยแกน่ สารสินธุ์โดยภาพรวมอยู่ในระดับมาก เรียงลำดับค่าเฉลี่ยจากมากไปหาน้อย ดังนี้คือ ด้านคุณภาพการให้บริการ ด้านประสิทธิผลของการปฏิบัติงาน ด้านประสิทธิภาพของการปฏิบัติราชการ และด้านการกำกับดูแลและการพัฒนาองค์การ ตามลำดับ 2) ปัจจัยที่มีอิทธิพลต่อประสิทธิผลการปฏิบัติงานของเทศบาลตำบลกลุ่มพัฒนาจังหวัดร้อยแก่นสารสินธุ์ ได้แก่ ปัจจัยภายในองค์การ มากที่สุดคือ วัฒนธรรมองค์การที่มีประสิทธิภาพ สมรรถนะการบริหารจัดการการพัฒนาทรัพยากรมนุษย์อย่างต่อเนื่อง การติดตามและประเมินผลอย่างต่อเนื่อง ตามลำดับ ปัจจัยด้านบุคลากรมากที่สุดคือ สมรรถนะผู้นำองค์กร ความรู้ ความสามารถของบุคลากร แรงจูงใจใฝ่สัมฤทธิ์ของบุคลากร การสนับสนุนจากผู้บริหาร ความรับผิดชอบของผู้ปฏิบัติงาน ตามลำดับ และปัจจัยภายนอกองค์การมากที่สุดคือ การตรวจสอบจากหน่วยงานกำกับ นโยบายส่งเสริมและสนับสนุนจากภาครัฐ และการมีส่วนร่วมของประชาชน ตัวแปรดังกล่าวสามารถพยากรณ์ประสิทธิผลการการพัฒนาขีดสมรรถนะบุคลากรสายวิชาการได้ร้อยละ 97.20 (R2 = 0.972 , F = 854.704) อย่างมีนัยสำคัญทางสถิติที่ระดับ .05 และ 3) ตัวแบบพัฒนาประสิทธิผลการดำเนินงานของเทศบาลตำบลกลุ่มพัฒนาจังหวัดร้อยแก่นสารสินธุ์ ประกอบด้วยองค์ประกอบ 3 องค์ประกอบ ได้แก่ 1) กระบวนการพัฒนาระบบการให้บริการประชาชน 2) การพัฒนาองค์การให้มีขีดสมรรถนะสูงและทันสมัย และ 3) การยกระดับความโปร่งใสและสร้างความเชื่อมั่นศรัทธาในการบริหารราชการแผ่นดิน คำสำคัญ : ตัวแบบพัฒนา, เทศบาลตำบล, ประสิทธิผลการปฏิบัติงาน ABSTRACT The aims of the research were to assess job performance efficiency of sub-district municipalities; to analyze the causal factor affecting the job performance efficiency and to establish a development model for accounting for job performance efficiency of sub-district municipalities in the Roi-Kaen-Sarn-Sin Provincial Cluster. The research was divided into three phases. Phase 1: The research focused on assessing the job performance efficiency and analyzing causal factors contributing the job performance efficiency of the sub-district municipalities. The mixed research method was used for the study. The samples were 2,400 representatives consisting of executives, municipality members, municipal clerks, directors of the finance division, directors of the technician division, and people from 249 municipalities. The data analysis was computed by the descriptive statistics and Path Analysis was employed for data analysis. In-depth interview was used for the qualitative research, of which the targeted purposive sampling was 12 persons consisting of experts and related academics. The content analysis was used for the study. Phase 2: The research took a focus on designing the model of the job performance efficiency. Phase 3: The research dealt with affirming the model of the job performance efficiency of sub-district municipalities by 20 verification experts. The data analysis was computed by the descriptive statistics. Results of the research were as follows: 1) The overall job performance efficiency of sub-district municipalities in the Roi-Kaen-Sarn-Sin Provincial Cluster was at a high level in the following descending fashion: the service quality, efficiency of the job performance, effectiveness of the job performance, as well as monitoring and developing of the organization respectively 2) In addition, the factors affecting the job performance efficiency of the sub-district municipalities in the Roi-Kaen-Sarn-Sin Provincial Cluster were internal factors of the organization, of which the highest rated factors could be listed in descending way: effective organizational culture, management competency, regular human resource development and continuous evaluation respectively. Five high rated items of the factors were competency of leaders, knowledge and abilities of the municipality personnel, achievement motivation of the personnel, executives’ support and responsibilities respectively. Regarding the external factors, the three high rated items of the factors were accountability controlled by the public organization, public policies and public participation. The variables predicted the variance of the job performance efficiency of sub-district municipalities in the Roi-Kaen-Sarn-Sin Provincial Cluster was statically significant 97.20% (R2 = 0.972 , F = 854.704) at the .05 level and 3) The model for developing the job performance efficiency of the sub-district municipalities in the Roi-Kaen-Sarn-Sin Provincial Cluster consisted of three components: 1) a process of the public service system, 2) excellence and competencybased organization development, 3) upgraded transparency and confidence in public administration. Keywords : Model for Development, Sub-District Municipalities, Job Performance Efficiency